Pollen and microsporangium development in Hovenia dulcis (Rhamnaceae): a different type of tapetal cell ultrastructure - Gotelli, Marina María (2016)
Despite that there is some literature on pollen morphology of Rhamnaceae, studies addressing general aspects of the microsporogenesis, microgametogenesis, and anther development are rare. The aim of this paper is to describe the ultrastructure of pollen grain ontogeny with special attention to tapetum cytology in Hovenia dulcis. Anthers at different stages of development were processed for transmission and scanning electron microscopy, bright-field microscopy, and fluorescence microscopy. Different histochemical reactions were carried out. The ultrastructural changes observed during the development of the tapetal cells and pollen grains are described. Large vesicles containing carbohydrates occur in the tapetal cell cytoplasm during the early stages of pollen development. Its origin and composition are described and discussed. This is the first report on the ontogeny and ultrastructure of the pollen grain and related sporophytic structures of H. dulcis.